Bionic universal accurate self-repairing anti-corrosion coating

By using crosslinked double-layer electrospinned nanofiber networks and photothermal induction materials in the self-healing coating, precise in-situ repair and continuous repair agent supply in extreme environments are achieved, and the problem of inefficient repair in the prior art is solved.

CN119711190AInactive Publication Date: 2025-03-28JILIN UNIVERSITY

Patent Information

Application Number
CN202411630606.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing self-repair coatings are difficult to achieve accurate in-situ repair in extreme environments, and the supply of repair agents is insufficient, resulting in ineffective repair efficiency.

Method used

A crosslinked double-layer electrospinning nanofiber network is used as a repair carrier and transportation channel, a bottom load corrosion probe, and a top load photothermal sensing material, which realizes self-healing through near-infrared light excitation.

Benefits of technology

Accurate in-situ repair in extreme environments, and the repair agent is continuously supplied through a continuous transmission network, significantly improving the repair efficiency and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711190A_ABST
    Figure CN119711190A_ABST
Patent Text Reader

Abstract

The invention discloses a bionic general accurate self-repairing anti-corrosion coating layer. According to the invention, a cross-linked through vein network is used as a bionic prototype, a nutrient conveying mechanism is explored, a double-layer cross-linked nanofiber network structure is constructed by using a self-repairing polymer, and corrosion self-early warning and accurate in-situ self-repairing functions are integrated and compounded. According to the coating, a corrosion site is accurately positioned through visual indication, the temperature of a damaged site is driven to be rapidly increased by utilizing remote near-infrared light, migration and flowing of self-repairing fibers along a transportation network can be triggered, and rapid and accurate in-situ self-repairing is realized. Based on the vein network type cross-linked nanofiber repairing carrier and the conveying channel, the self-repairing system can continuously convey a repairing agent to a damaged site repeatedly, and the problem that a traditional self-repairing system is insufficient in repairing agent supply is solved. And due to a quick and controllable photo-thermal repairing mechanism, the device can realize repeated and accurate in-situ repairing under extreme conditions of low temperature, seawater, vacuum, strong acid, strong alkali and oxidation reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of self-repairing anti-corrosion coatings, and in particular relates to a bionic universal and precise self-repairing anti-corrosion coating. Background Art

[0002] So far, there have been many studies on the design and preparation of self-healing coatings on the surface of metal corrosion and fouling, but the vast majority of self-healing functional surface repair treatments are relatively complex and cannot selectively trigger repair behavior on demand during actual application, that is, it is impossible to achieve precise in-situ repair of designated corrosion sites; and when facing extreme environments, traditional self-healing systems are prone to lose their self-healing anti-corrosion effectiveness. Extreme corrosive environments, such as high humidity, low temperature, high salt, vacuum, and strong acids and alkalis, will greatly increase the resistance to repair, delay the progress of repair, and even cause repair failure. When the coating is damaged underwater, water molecules may inhibit the repair process by saturating hydrogen bonds, coordinating with metal cations, or dissolving the repair agent; in addition, under freezing conditions, the thermal dynamic trend of the repair factor is significantly reduced, resulting in a significant decrease in the repair performance. Therefore, there are certain challenges in developing composite anti-corrosion coatings with universal extreme environment resistance and self-healing properties. In addition, limited loading and insufficient supply of the repair agent are also the main obstacles to limiting the repair performance. Most repair systems can only achieve one-time repair behavior at the defect site, and lack continuous transmission channels to repeatedly and continuously supply the repair agent. Therefore, constructing a repair agent transport network inside the coating is the key to solving this problem; at the same time, the combined precise positioning corrosion monitoring system and the universal precise in-situ self-repair strategy will further enhance its corrosion resistance. Summary of the invention

[0003] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, and inspired by the plant vein network transport system, the present invention uses a cross-linked double-layer electrospun nanofiber network as a repair carrier and transport channel to prepare a universal and precise in-situ self-repairing anti-corrosion coating. The technical solution adopted by the present invention is as follows: A universal and precise in-situ self-repairing anti-corrosion coating, which has a double-layer cross-linked network constructed by self-repairing nanofibers as a structural framework, wherein the double-layer cross-linked network is formed by the nanofibers being cross-linked with each other, and the double-layer cross-linked network is composed of a bottom layer and a top layer, wherein the bottom layer carries a corrosion probe and the top layer carries a photothermal sensing material; The corrosion probe senses the corrosion change and generates obvious fluorescence intensity or color change, accurately locating the corrosion damage site; the photothermal sensing material gives the composite coating excellent photothermal conversion ability, and the temperature of the area irradiated by near-infrared light rises rapidly, driving the self-repairing fiber along a preset path or selectively triggering a precise in-situ repair process on demand at a designated damage site; The nanofiber is made of a self-repairing polymer, and the self-repairing polymer is a combination of one or more self-repairing polymers selected from thermoplastic polyurethane, polycaprolactone, polylactic acid, polystyrene, polyvinyl chloride, and polyethylene; Preferably, the corrosion probe is a combination of one or more of 8-hydroxyquinoline, phenolphthalein, methyl orange, thymol blue, o-phenanthroline, tannic acid, dopamine, rhodamine B and derivatives thereof.

[0004] Preferably, the photothermal induction material is a combination of one or more of graphene, graphene oxide, carbon nanotubes, graphite, carbon black, ferrosoferric oxide nanoparticles, and carbonyl iron powder.

[0005] Preferably, the double-layer cross-linked network is also coated with a polymer resin coating, and the polymer resin is a combination of one or more of epoxy resin, acrylic resin, silicone resin, and polyurethane.

[0006] The present invention provides a method for preparing a bionic universally precise self-repairing anti-corrosion coating, comprising the following preparation steps: (1) Preparation of precursor solution A: A self-healing polymer solution with a concentration of 10-30 wt% is prepared, and the corrosion probe is added to the self-healing polymer solution in a mass ratio of (1-3):10, and stirred to obtain a precursor solution A; (2) Preparation of precursor solution B: A photothermal induction material dispersion is prepared at a concentration of 5-20 mg / mL, and then a self-healing polymer is added to make the concentration of the self-healing polymer 10-30 wt %, and the mixture is stirred evenly to obtain a precursor solution B; (3) Precursor solution A and precursor solution B were used for electrospinning in sequence for 10-30 min and 40-80 min, respectively, to obtain a double-layer fiber network that was cross-linked and interconnected. The electrospinning conditions were: output voltage >10 kV, flow rate >1 μL / min, receiving distance 5-100 cm, and the diameter of the prepared self-healing nanofibers was ≤1 μm.

[0007] The solvent of the self-healing polymer solution in step (1) and the photothermal induction material dispersion in step (2) is preferably a combination of one or more of acetone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, toluene and cyclohexane.

[0008] Preferably, in step (2), the photothermal sensing material is evenly dispersed in the solvent by ultrasonic treatment in a cell disruptor for 5 to 60 minutes; Preferably, the method further comprises step (4) coating a polymer resin and performing a curing treatment.

[0009] The polymer resin solution is applied to the surface of the double-layer fiber network structure by drip coating, spin coating or spray coating, and after solidification, a polymer resin coating is formed on the surface.

[0010] The polymer resin is a combination of one or more of epoxy resin, acrylic resin, silicone resin and polyurethane. Different curing temperatures and times are used for treatment according to the selected polymer resin.

[0011] The mass ratio of solute to solvent in the polymer resin solution is (0.8~1.5):10, so that the polymer resin needs to have good fluidity and diffusivity.

[0012] The solvent in the polymer resin solution is a mixed liquid of one or more of water, ethanol, ethyl acetate, butyl acetate, tetrahydrofuran and chloroform.

[0013] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses the plant reticular veins as a bionic prototype to study its transport mechanism for water and inorganic salts; on this basis, a double-layer nanofiber network that is cross-linked and interconnected is constructed, and used as a repair carrier and transmission channel to achieve continuous transmission and continuous supply of the repair agent.

[0014] (2) Compared with the multifunctional composite coating prepared by layer-by-layer coating, the present invention utilizes self-healing polymers to encapsulate different functional molecules to construct a double-layer nanofiber network structure with specific interlayer functions, and combines it with coating technology to achieve good interface compatibility between functional layers. At the same time, it integrates the dual functions of corrosion self-warning and universal and precise in-situ self-repair to enhance the corrosion resistance of the composite coating and metal materials and extend their service life.

[0015] (3) The corrosion probe loaded on the bottom layer can realize in-situ corrosion warning of one or more of iron, copper, magnesium, aluminum and their alloys, as well as carbon steel and stainless steel. The corrosion probe will produce obvious fluorescence intensity or color changes after sensing corrosion changes, accurately locating the corrosion damage site; in addition, the corrosion indicator is deposited on the exposed metal surface after coordination with the metal ions to form an active protective layer, which can block the contact and interaction between the corrosive medium and the metal substrate, and effectively inhibit further corrosion reactions. The active corrosion inhibition function and the precise in-situ coating substrate repair can synergistically enhance the long-term corrosion resistance of the composite coating.

[0016] (4) The photothermal induction material gives the composite coating excellent photothermal conversion ability. The temperature of the area irradiated by near-infrared light rises rapidly, driving the migration and flow of the self-repairing fibers, and a good repair effect can be achieved within 30 seconds. Under the remote control of near-infrared light, the coating can selectively trigger the precise in-situ repair process along a preset path or at a specified damaged site on demand without affecting the original performance of the undamaged area of ​​the coating. In addition, it exhibits a general resistance to extreme environmental repair performance, and can achieve precise in-situ repair under low temperature (-40~4℃), underwater, low-temperature salt water (1~10wt% NaCl solution at-40~4℃), vacuum (-1.2~-0.5MPa) and strong acid and alkali (pH=2~13) conditions.

[0017] (5) The present invention overcomes the disadvantage of sacrificing the mechanical stability of the coating to achieve efficient repairability. After the coating is compounded with an unmodified polymer resin, the stability of the self-repairing nanofibers can be guaranteed, while achieving higher substrate adhesion, interlayer adhesion and mechanical stability, and has good application prospects in corrosion protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the double-layer nanofiber network structure; Figure 2 This is a scanning electron microscope image of a double-layer nanofiber network structure; Figure 3 The transmission electron microscope image of the top layer loaded with multi-walled carbon nanotube nanofibers; Figure 4 The adhesion strength and shear strength of the double-layer nanofiber composite coating; Figure 5 This is a diagram of the repair process of the double-layer nanofiber composite coating within 30 seconds; Figure 6 To provide a precise in-situ restoration process diagram; Figure 7 It is the fluorescence image under the excitation of 365nm ultraviolet lamp; Figure 8 Schematic diagram and scanning electron microscope image of the precise in-situ repair process that can withstand extreme environments. DETAILED DESCRIPTION

[0019] The technical solution adopted by the present invention is further explained and illustrated in the following in the form of specific embodiments in combination with the accompanying drawings.

[0020] Example 1 1) Using CHCl3 and DMF with a volume ratio of 0.8:1 as solvent, add 1 g of polycaprolactone (PCL) particles, completely dissolve under mechanical stirring at 40 °C, then add 100 mg of 8-hydroxyquinoline (8HQ) and continue stirring for 24 h to obtain a bottom fiber precursor polymerization solution.

[0021] 2) Multi-walled carbon nanotubes (CNTs) were uniformly dispersed in a mixed solvent of CHCl3 and DMF with a volume ratio of 1:1 using a cell disrupter for 5-60 min. The concentration was 10 mg / mL. 4 mL of the dispersion was extracted, 1 g of PCL was added, and mechanical stirring was performed at 40 °C for 24 h to obtain a top-layer fiber precursor polymerization solution.

[0022] 3) The electrospinning conditions are: output voltage>10kV, flow rate>1μL / min, receiving distance of 5~100cm; the bottom and top polymer solutions obtained in step 1) and step 2) are electrospun for 20min and 60min respectively to prepare a double-layer nanofiber network structure (such as Figure 1 ), the diameter of the prepared nanofibers is ≤1μm.

[0023] 4) Using ethanol as a diluent and polyetheramine D230 as a curing agent, epoxy resin was coated on the double-layer fiber membrane, and excess epoxy resin was removed by spin coating at a speed of 3000 rpm for 30 seconds, and then cured at room temperature for 2 days to obtain a dual-functional nanofiber composite coating.

[0024] Example 2 The difference between this embodiment and embodiment 1 is that: 50 mg of 8-hydroxyquinoline is added in step 1).

[0025] Example 3 The difference between this embodiment and embodiment 1 is that: step 2) extracting 0.8 mL of dispersion liquid.

[0026] Example 4 The difference between this embodiment and embodiment 1 is that: Step 2) extracting 2.4 mL of dispersion liquid.

[0027] Example 5 The difference between this embodiment and embodiment 1 is that: Step 2) 5.6 mL of dispersion liquid is extracted.

[0028] Example 6 The difference between this embodiment and embodiment 1 is that: in step 2), the concentration of the multi-walled carbon nanotubes in the dispersion is 20 mg / mL.

[0029] In addition to the above embodiments, in other embodiments of the present invention, thermoplastic polyurethane (TPU), polylactic acid (PLA), polystyrene, polyvinyl chloride, and polyethylene are used to replace polycaprolactone, which have the same or similar effects.

[0030] In other embodiments of the present invention, phenolphthalein, methyl orange, thymol blue, o-phenanthroline, tannic acid, dopamine, and rhodamine B are used instead of 8-hydroxyquinoline, with the same or similar effects. It is conceivable that the derivatives of the above compounds should also have the same or similar effects.

[0031] In the above embodiment, the photothermal induction material is multi-walled carbon nanotubes. Other materials having the same function include graphene, graphene oxide, single-walled carbon nanotubes, graphite, carbon black, ferrosoferric oxide nanoparticles and carbonyl iron powder.

[0032] The solvent used for the self-healing polymer solution and the dispersed photothermal sensing material in the present invention is selected from a mixed solvent of one or more of acetone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, toluene and cyclohexane.

[0033] The polymer resin coating coated on the surface of the double-layer cross-linked network may be, in addition to the epoxy resin given in the embodiment, acrylic resin, silicone resin, polyurethane or a composite coating of multiple resins thereof, and the corresponding solvent may be one or more mixed liquids of water, ethanol, ethyl acetate, butyl acetate, tetrahydrofuran, and chloroform. In addition, the coating method of the polymer resin coating includes various methods such as drop coating, spin coating, and spray coating.

[0034] Effect verification: Figure 2 The figure shows the scanning electron micrograph of the double-layer nanofiber network structure. It can be observed that the nanofibers with diameters of 263nm to 789nm form a network structure by cross-linking with each other. Figure 3 This is a transmission electron microscopy image of a nanofiber loaded with multi-walled carbon nanotubes on the top layer. It can be observed that a number of multi-walled carbon nanotubes are loaded inside the nanofiber filaments.

[0035] In the present invention, the epoxy resin coating gives the nanofiber composite coating excellent mechanical stability ( Figure 4 ). The adhesion strength between the composite coating and the substrate was characterized by a universal material testing machine. Compared with pure epoxy coating, the presence of nanofiber membrane leads to a decrease in the adhesion strength of the composite coating, but it still has a high adhesion strength of 7.13 MPa, showing good adhesion stability and has good application prospects in the field of engineering corrosion protection.

[0036] In the present invention, the photothermal induction material endows the composite coating with excellent photothermal conversion ability. Under the drive of long-range near-infrared light, the temperature of the local area of ​​the composite coating rises rapidly, triggering the rapid migration and flow of PCL nanofibers along the transport channel. Figure 5As shown, Example 1 can achieve rapid self-repair within 30 seconds. In addition, its repair behavior is precisely controllable and can achieve selective in-situ repair along a preset path or at a designated location. When near-infrared light is applied to the corrosion damage site, the temperature of the local area of ​​the radiation rapidly increases, triggering the migration and flow of the PCL repair agent and quickly filling the gaps at the defect site, achieving precise in-situ self-repair. Figure 6 The top-down repair process of the scratches on the nanofiber composite coating in Example 1 was demonstrated. As can be seen from the figure, the damaged sites within the near-infrared light radiation area restored to the original closed state, while scratches still existed in the areas outside the radiation range, proving that it can achieve precise repair of local sites in a non-contact remote control manner. After scanning from top to bottom with near-infrared light, the passive barrier properties of the composite coating were precisely repaired in situ without interfering with the original properties of the surrounding intact parts.

[0037] In the present invention, the bottom nanofiber membrane can quickly release 8HQ molecules in a pH sensing manner to react with the Al2O3 produced by corrosion. 3+ After coordination, there is a significant fluorescence enhancement effect, which can realize the early corrosion monitoring of metal aluminum and aluminum alloys ( Figure 7 ); At the same time, the complex film is deposited on the metal surface to form an active protective layer to inhibit further corrosion reactions.

[0038] In the present invention, the nanofiber composite coating has a general extreme environment resistance repair effect. Figure 8 As shown in the figure, the damaged nanofiber composite coating was placed in extreme environments such as low temperature (-40~4 ℃), underwater, low-temperature saline (1~10wt% NaCl solution at-40~4 ℃) and vacuum (-1.2~-0.5 MPa), and the defect site was remotely irradiated with near-infrared light. Even with enhanced repair resistance, the composite coating achieved precise in-situ repair within 30 s.

Claims

1. A universal and precise in-situ self-repairing anti-corrosion coating, characterized in that: The coating uses a double-layer cross-linked network constructed by self-repairing nanofibers as a structural framework. The double-layer cross-linked network is formed by the nanofibers being cross-linked with each other, and the double-layer cross-linked network consists of a bottom layer and a top layer, wherein the bottom layer carries a corrosion probe and the top layer carries a photothermal sensing material. The corrosion probe senses the corrosion change and generates obvious fluorescence intensity or color change, accurately locating the corrosion damage site; the photothermal sensing material gives the composite coating excellent photothermal conversion ability, and the temperature of the area irradiated by near-infrared light rises rapidly, driving the self-repairing fiber along a preset path or selectively triggering a precise in-situ repair process on demand at a designated damage site; The nanofiber is made of a self-repairing polymer, and the self-repairing polymer is a combination of one or more self-repairing polymers selected from thermoplastic polyurethane, polycaprolactone, polylactic acid, polystyrene, polyvinyl chloride and polyethylene.

2. The universal and precise in-situ self-repairing anti-corrosion coating according to claim 1, characterized in that: The corrosion probe is a combination of one or more of 8-hydroxyquinoline, phenolphthalein, methyl orange, thymol blue, o-phenanthroline, tannic acid, dopamine, rhodamine B and derivatives thereof.

3. The universal and precise in-situ self-repairing anti-corrosion coating according to claim 1, characterized in that: The photothermal sensing material is a combination of one or more of graphene, graphene oxide, carbon nanotubes, graphite, carbon black, ferroferric oxide nanoparticles, and carbonyl iron powder.

4. The universal and precise in-situ self-repairing anti-corrosion coating according to claim 1, characterized in that: The surface of the double-layer cross-linked network is also coated with a polymer resin coating, and the polymer resin is a combination of one or more of epoxy resin, acrylic resin, silicone resin, and polyurethane.

5. A method for preparing a bionic universally precise self-repairing anti-corrosion coating as claimed in claim 1, characterized in that: The method comprises the following preparation steps: (1) Preparation of precursor solution A: A self-healing polymer solution with a concentration of 10-30 wt% is prepared, and the corrosion probe is added into the self-healing polymer solution at a mass ratio of (1-3) : 10, and stirred evenly to obtain a precursor solution A; (2) Preparation of precursor solution B: A photothermal induction material dispersion is prepared at a concentration of 5-20 mg / mL, and then a self-healing polymer is added to make the concentration of the self-healing polymer 10-30 wt %, and the mixture is stirred evenly to obtain a precursor solution B; (3) Precursor solution A and precursor solution B were used for electrospinning in sequence for 10-30 min and 40-80 min, respectively, to obtain a double-layer fiber network that was cross-linked and interconnected. The electrospinning conditions were: output voltage >10 kV, flow rate >1 μL / min, receiving distance 5-100 cm, and the diameter of the prepared self-healing nanofibers was ≤1 μm.

6. The method for preparing the bionic universal precise self-repairing anti-corrosion coating according to claim 5, characterized in that: The solvent of the self-healing polymer solution in step (1) and the photothermal induction material dispersion in step (2) is a combination of one or more of acetone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, toluene and cyclohexane.

7. The method for preparing the bionic universal precise self-repairing anti-corrosion coating according to claim 5, characterized in that: In step (2), the photothermal sensing material is evenly dispersed in the solvent by ultrasonic treatment in a cell disruptor for 5 to 60 minutes.

8. The method for preparing the bionic universal precise self-repairing anti-corrosion coating according to claim 5, characterized in that: The method further comprises step (4) coating a polymer resin and performing a curing treatment: Applying the polymer resin solution to the surface of the double-layer fiber network structure by drip coating, spin coating or spray coating, and forming a polymer resin coating on the surface after curing; The polymer resin is a combination of one or more of epoxy resin, acrylic resin, silicone resin and polyurethane; different curing temperatures and times are used for treatment according to the selected polymer resin.

9. The method for preparing the bionic universal precise self-repairing anti-corrosion coating according to claim 8, characterized in that: The mass ratio of solute to solvent in the polymer resin solution is (0.8~1.5):

10.

10. The method for preparing the bionic universal precise self-repairing anti-corrosion coating according to claim 9, characterized in that: The solvent in the polymer resin solution is a mixed liquid of one or more of water, ethanol, ethyl acetate, butyl acetate, tetrahydrofuran and chloroform.

Citation Information

Patent Citations

  • Multifunctional core-shell self-repairing electrostatic spinning material as well as synthesis method and application thereof

    CN113930859A

  • Self-early-warning coaxial electrostatic spinning fiber as well as preparation method and application thereof

    CN114574977A

  • Photo-thermal response nanofiber self-repairing coating and preparation method thereof

    CN114618760A

  • Photoresponsive self-repairing nanofiber and preparation method thereof

    CN116536784A

  • Self-repairing and self-early-warning coating based on photo-thermal trigger phase change and preparation method of self-repairing and self-early-warning coating

    CN118685093A

Cited By

  • A preparation method of a self-repairing coating with fluorescent labeling and photothermal synergistic conversion

    CN122517256A